Climate Change and Cultural Heritage: From Small- to Large-Scale Effects—The Case Study of Nora (Sardinia, Italy) - Sitzia, Fabio (MDPI, 2022)
Rising sea levels are mainly due to increases in environmental temperatures that are causing ice to melt. The weathering of geomaterials is mainly due to the increase in the concentration of greenhouse gases in the atmosphere. This research addresses current and future sea level rises and their weathering effects on the building stones in the Phoenician–Punic archaeological area of Nora (Sardinia, Italy). Some forecasting models, selected according to real-world scenarios (shared socioeconomic pathways—SSPs), give a definitive overview of both the rising sea levels and stone weathering conditions in Nora. The year 2100 A.D. was selected as the base of our investigations because the SSPs are scenarios of projected socioeconomic global changes up to 2100 A.D. The data on the expected alteration of geomaterials were reconstructed by considering the temperatures, the rainfall amount, and the atmospheric CO2 of every scenario. This was made possible by knowing the current degree of alteration of the geomaterials and their weathering resistance. The rising sea level models were obtained through the SSPs scenarios data and built using geographic information systems software. The projections show a slowing down of the weathering degrees of the stone materials in Nora. This is due to the increase in the average annual temperature and the decrease in the average annual rainfall. However, it is shown that some other factors, such as the marine spray in the area, could accelerate the decay. Projections of the rising sea levels show how the settlement will be partially submerged, losing between 3.54% and 8.49% of the emerged land. The models provided a maximum ingression of the coastline, ranging from 23.7 m to 29.5 m, based on the severity of the scenarios. Coastline-shifting maps indicate the flooding of some buildings located on the western coast of Nora, the most sensitive part of the territory.
Keywords: geoarchaeology; sea level rise; climate change; cultural heritage; ancient mining activity; shared socioeconomic pathways